Complex Immune Correlates of Protection in HIV-1 Vaccine Efficacy Trials - Tomaras, Georgia D. (Immunol Rev, 2017)
Development of an efficacious HIV-1 vaccine is a major priority for improving human health worldwide. Vaccine mediated protection against human pathogens can be achieved through elicitation of protective innate, humoral, and cellular responses. Identification of specific immune responses responsible for pathogen protection enables vaccine development and provides insights into host defenses against pathogens and the immunological mechanisms that most effectively fight infection. Defining immunological correlates of transmission risk in preclinical and clinical HIV-1 vaccine trials has moved the HIV-1 vaccine development field forward and directed new candidate vaccine development. Immune correlate studies are providing novel hypotheses about immunological mechanisms that may be responsible for preventing HIV-1 acquisition. Recent results from HIV-1 immune correlates work has demonstrated that there are multiple types of immune responses that together, comprise an immune correlate—thus implicating polyfunctional immune control of HIV-1 transmission. An in depth understanding of these complex immunological mechanisms of protection against HIV-1 will accelerate the development of an efficacious HIV-1 vaccine.